(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The purpose of this study was to describe the 5 levels of students’ mental models, namely initial, transition 1, synthesis, transition 2 and formal understanding of the quadrilateral concept. The subjects of this study were students of 7nd grades, which amounted to 34 students, but there were only 5 students who were representatives in each level of the mental model. The results of this study are students with this initial level do not have the concept of a quadrilateral in themselves or the concept that is in them cannot be recalled when they answer the questions given. At transition level 1, student is able to answer correctly using the concepts that are in him. So when describing the answer is also close to the truth. For student who are at the synthesis level, they have started to be able to answer correctly with a concept model that is starting to form perfectly. Student who is at transition level 2 is already close to the truth both in answering and describing the answers in his self-concept about quadrilaterals. Student with a formal mental model level has a perfect quadrilateral concept and can use the concept well in answering the questions given. In describing the answers that have been written are also correct and the answers given can be accepted scientifically.